Manufacturability of structure in selective laser melting for quuality assurance - Nicole Dominique Savia De Rozario (2015)
This project aimed to generate theoretical graphs relating expected relative densities to energy densities of three metals commonly fabricated using Selective Laser Melting (SLM), and one graph relating strut variance thickness to the energy density of Ti6Al4V, a metal that is commonly fabricated by SLM and used for orthopaedic implants. This project also aims to analyse the validity of current density test methods to assess the quality of parts fabricated using Additive Manufacturing (AM). SLM is a relatively new additive manufacturing process that builds parts layer-by-layer by fusing powder particles using laser. Parts are based three-dimensional computer-aided designed models. SLM is capable of producing fully functional parts containing complex internal and external geometries in a single manufacturing step. This saves in time and cost, making it popular as a manufacturing technique. Its capability for low volume and mass customisation production make it suitable for application in the aerospace and biomedical fields, where products can be tailored to patients’ specific needs. However, application is limited due to the lack of a recognised international standard in measuring techniques of parts produced by AM. In this report, data from previous studies were collected and consolidated to form graphs that provide information of expected mechanical properties for a given set of parameters. Samples were fabricated and undergone several tests to validate the graphs. Simultaneously, these test methods were assessed for their repeatability and validity in measuring samples produced using SLM. Graphs generated, while give an idea of the expected relative densities of various parameters, must be given an allowance to account for variables not previously considered such as powder size and quality. Analysis of data showed that the Archimedes’ principle has a high rate of repeatability, with deviation of less than 1%.